TINGKAT KANDUNGAN UNSUR RADIOAKTIF AIR SUNGAI AYUNG DI DENPASAR BALI - Alit Ardana, Dewa Nyoman; Budiarsa Suyasa, I Wayan; Sundra, I Ketut (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 3 No 1, 2012)
Ayung river is one of the longest rivers in Bali. The upstream of the river is in regency of Bangli, Badung, Buleleng, Tabanan and downstream is located in Padang Galak beach, East Denpasar Sub-regency. As the sample of the study, the water of the river was taken from the stream entering the city of Denpasar. The sample was taken in five different points and for each point was taken twice. The first was taken at 5 p.m, and the second was at 6 a.m. This study aims at finding out the rate of radioactive content of Ayung river water in the city of Denpasar. The water sample was analyzed in Radiometry Analysis Group of Radiation Physics and environmental research centre and Nuclear Technique Development, Jalan Taman Sari 71 Bandung – 40132. The process of counting was conducted in this place in order to know the rate of the element activities and then identification of elements contens in the sample. The result of the counting and identifying was compered with standard grade of radioactivity in the area. The element of identification result and the amount of activity rate found showed that the element were natural radioactive elements, the content: 40K (Kalium-40), 234Th (Thorium-234), 233Th (Thorium-233), 228Ac (Actinium-288), 114mIn (Indium-114m). The highest activity of radioactive elements in each sample point: in E2 point content element 40K with the activity 2.08 Bq/lt, in point A1 234Th with the activity 16.34 Bq/lt, in point E1 containts 233Th with activity 598.29 Bq/lt, in point E1 and E2 contain 228Ac with the activity 939.63 Bq/lt. The height of activity value of the counting and identifying elements was still under the rate of the highest level. The result of the study showed that radioactive elements 40K had the tendency of increasing radioactivity. The same thing happened to 233Th at the peak of energi 185.00 keV. The content of its radioactive tends to exist in each point of sample point and the activity tends to increase. Though the rate of radioactivity content was still under the highest permitted level (1x104 Bq/lt for 40K and 7x102 for 233Th) bu the case needs to be watched out that the dangerus grade pollution would take place.
Keywords: River water, radioactive, content rate